(In)determinacy, bargaining, and R&D policies in an economy with endogenous technological change - Chung-hui Lai (Kiel Institute for the World Economy (IfW), 2013)
In this paper, the author shows how the introduction of a bargaining game structure into a standard R&D endogenous growth model can be a potential source of local indeterminacy. He also shows that on a high-growth path, the government, by directly engaging in R&D activities and using R&D subsidies, may not enhance economic growth. On a low-growth path, the government, by directly engaging in R&D activities and using R&D subsidies, may enhance economic growth.
Keywords: O30; O41; L00; 330; government R&D; innovation; endogenous growth; bargaining; indeterminacy